Arthroscopic Distal Clavicle Resection for an Acromioclavicular Ganglion Cyst with Cuff Tear Arthropathy: A Case Report. Issue 2 (6th April 2022) - Fujii, Yuto; Matsumura, Noboru; Furuhata, Ryogo; Kimura, Hiroo; Suzuki, Taku; Iwamoto, Takuji; Matsumoto, Morio; Nakamura, Masaya
Abstract : Case: A 77-year-old man with an acromioclavicular joint ganglion cyst with cuff tear arthropathy had a large mass in the left shoulder. Arthroscopic distal clavicle resection successfully relieved his symptoms without loss of shoulder function by enlargement of the bypass between the cyst and subacromial space through the acromioclavicular joint. Conclusion: Arthroscopic distal clavicle resection can remove a 1-way check valve in a minimally invasive manner. This case indicated that arthroscopic distal clavicle resection could be a useful treatment option for patients with acromioclavicular joint ganglion cysts with functional but irreparable rotator cuff tears.